Analysis of Student's Coping Strategies in German Language Learning Anxiety at Senior High School 3 Yogyakarta - Evita Aulia Nur Rohmah; Iman Santoso (Nexus Publishing, 2025)
This study aims to identify the coping strategies used by students at SMA Negeri 3 Yogyakarta, a PASCH school, in dealing with anxiety during German language learning. Foreign language learning anxiety is an obstacle that can affect the learning process and students’ academic performance. This research employed a descriptive qualitative approach with a case study method. The research subjects included all students enrolled in German language classes, specifically students from class XI IPA 3 and class XII IPA 4. Data were collected through interviews, observations, and questionnaires involving both students and the German language teacher. The data were analyzed through the stages of data reduction, data display, and conclusion drawing.The results indicate that students apply coping strategies consisting of problem-focused coping, such as reviewing materials, seeking additional resources like learning apps, and asking for help from teachers or peers, as well as emotion-focused coping, such as positive thinking, accepting mistakes as part of the learning process, and engaging in relaxation activities like listening to music or other calming routines. Problem-focused coping was found to be more effective in improving students’ understanding and learning outcomes compared to emotion-focused coping. These findings highlight the importance of implementing interactive teaching methods, providing positive affirmation from teachers, and fostering a supportive learning environment to reduce students’ anxiety and enhance their confidence and motivation in learning German.